Comparative assessment of myocardial function between late premature newborns and term neonates using the 2D speckle tracking method - Toma, Daniela; Făgărășan, Amalia; Cerghit-Paler, Andreea; Togănel, Rodica; Cucerea, Manuela; Săsăran, Maria Oana; Gozar, Liliana (Frontiers in Pediatrics, 2024)
Introduction: Assessment of myocardial function through speckle tracking echocardiography (STE) can bring benefits to conventional echocardiography in premature newborns, a particular vulnerable group in terms of adaptation to extra-uterine life. Furthermore, it represents a non-invasive imagistic method which can guide therapeutic approach in the hemodynamically unstable newborn. This study aims to highlight the particularities of myocardial function in late premature newborns, by conducting a comparison with a group of healthy neonates, by using STE.Methods: Conducted over a timespan of two years, this prospective study enrolled 64 term neonates and 21 premature newborns, with gestational ages ranging between 28 and 36 weeks, who prior to discharge underwent a cardiac ultrasound, involving two-dimensional image acquisitions of the apical four-chamber view of both ventricles. Afterwards, the images were offline analyzed, by using the autostrain function. Results: After segmental strain analysis, no significant discrepancies between the two groups in terms of interventricular values were found. However, left ventricle and right ventricle strain measurements differed significantly (p<0.01), for each of the analyzed segments (basal, medial or apical). Moreover, a linear increase in interventricular (IV) basal strain with corrected gestational age progression was noted (p=0.04). Peak global longitudinal strain (pGLS) and EF were similar between the two study groups. Premature newborns presented significantly more negative mean values of right ventricular free wall longitudinal strain (RVFWSL), (-24.19 ± 4.95 versus -18.05 ± 5.88, p<0.01) and of right ventricle global four chamber longitudinal strain (RV4CSL), (-19.71 ± 3.62 versus -15.46 ± 5.59, p<0.01), when compared to term neonates.The 2D STE is a reliable method for cardiac assessment of late preterm newborns. The evaluation of two-dimensional global longitudinal LV and RV strains might represent a useful tool in clinical practice. A better response of the right ventricle to the longitudinal deformation within premature neonates was noted. Thus, this study facilitates the identification of accurate reference values for this particular population segment, which will enable the evaluation of ventricular function in premature newborns with concurring disorders. Future longitudinal studies, assessing the fetal heart, could provide more insight into the development of myocardial function.